Effects of individual and combined exposure to sublethal doses to the pesticides Chlorpyrifos, Bifenthrin and Imidacloprid ondetoxification and neurotoxicity enzimes in Apis mellifera workers - Perezlindo, Tamara (2023)
The honeybee (Apis mellifera L.) is an important pollinator and a model for pesticide effects on insect pollinators. Bees can be exposed to multiple pesticides that mayinteract synergistically, amplifying their side effects. Some combinations show synergistic or antagonic combined effects that go far beyond what is predicted with currenteffect models. Up until now, only the combined additive effects of similar acting chemicals have been assessed accurately, whereas the combined effects of dissimilar actingchemicals have been greatly underestimated in many cases. In recent years, the mortality of bees, such as Apis mellifera, has become a strange global phenomenon that ishaving a negative impact given its great importance. The aim of this work was to analyze the impact of exposure to different agrochemicals for agricultural use in sublethaldoses and individually and in combination, on detoxification enzymes (Catalase (CAT) and Glutathione-S-transferase (GST)) and neurotoxicity (Acetylcholinesterase(AChe)). Bees up to 3 days old were collected and divided to carry out the different treatments, using 10 bees in each replicate. 10 ul of Bifenthrin (BIF), Chlorpyrifos(CLOR) and Imidacloprid (IMI) were applied topically in concentrations corresponding to LD10 (The range of concentrations used was based on previous studies ) asfollows: BIF; 2) CLOR; 3) IMI; 4) BIF+CLOR; 5) BIF+IMI; 6) IMI+CLOR; 7) CONTROL. After each treatment, the surviving bees were kept in a freezer at -80°C for theirsubsequent enzymatic analysis. The results obtained showed that for GST there is a significantly inhibition for all treatments with the control (p<0.05), except for theIMI+CLOR combination where there is no significant difference (p>0.05). For the CAT enzyme all treatments were significantly lower than the control (p<0.05). In the case ofAChE, the individual treatments of IMI, BIF, and CLOR as well as the IMI+CLOR combination were lower than the control (p<0.05) while the BIF+CLOR combination wasnot different from the control (p<0.05) and the IMI+BIF combination was significantly superior. These results report the synergistic (IMI+BIF for the AChe enzyme) andantagonistic (IMI+CLOR for GST and Ache) effects caused by simultaneous exposures to pesticide combinations in bees.